Problems of Sources for The Reconstruction of The History of Islam in Yauri Emirate - Salihu, Suwaiba; Yahaya, Atiku Garba (SCAD Independent, 2020)
The paper examined the challenges encountered during data collection in a field survey. There existed some variations between oral narratives and documented evidence on the history of Islam in Yauri Emirate. Management of such conflicting data from primary and secondary sources in academic research was one of the most tasking endeavors because it required corroboration people who witnessed the events and experts with authentic versions of the historical development of the event under investigation. Reconciling such data has become a daunting task for the researchers however when the researcher resorted to verification of the data collected from the experts and available old people in the community concerned, both data could be harmonized and produced robust findings in the reconstruction of Islamic history in Yauri Emirate.